2022
DOI: 10.7759/cureus.21492
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Audiometric Analysis in the Screening of Vestibular Schwannoma

Abstract: Introduction Asymmetric sensorineural hearing loss is the main early symptom of retrocochlear lesions, hence its importance in screening for vestibular schwannomas. Currently, there is no consensus regarding its definition. The objective was to identify the audiometric pattern that would serve as a predictor for vestibular schwannoma in patients with asymmetric hearing loss. Materials and methods A cross-sectional study was conducted that included patients with asymmetric heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Overall, the quality of included studies was low-to-moderate ( Table 2 ). Two studies found a high risk of bias in one domain (patient selection) [ 24 , 25 ]. For the rest of the domains, the risk of bias was assessed as low and unclear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the quality of included studies was low-to-moderate ( Table 2 ). Two studies found a high risk of bias in one domain (patient selection) [ 24 , 25 ]. For the rest of the domains, the risk of bias was assessed as low and unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The highest pooled sensitivity was achieved by the following protocols: Mangham 0.93 (95% CI: 0.76–0.98) [ 18 , 21 , 23 , 24 , 25 ], Amclass 0.93 (95% CI: 0.89–0.95) [ 18 , 22 , 23 , 24 , 25 ], and Nashville 0.91 (95% CI: 0.86–0.94) [ 18 , 20 , 22 , 24 , 25 ], while the highest pooled specificity and pooled positive likelihood ratio was achieved by the American Academy of Otolaryngology protocol (AAO) at 0.60 (95% CI: 0.49–0.70) and 2.1 (95% CI: 1.6–2.9) [ 18 , 20 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations